Improving Students’ Writing Skill through Outdoor Learning at SMA Negeri 1 Maiwa Kabupaten Enrekang - Hasan, Hasan (Maspul Journal of English Studies, 2019)
The objective of this research was intended to know whether or not using outdoor learning strategy can improve the students’ writing skill at SMA Negeri 1 Maiwa Kabupaten Enrekang. This research applied quasi experimental method with one class of experimental group and one class of control group. The researcher used pre-test and post-test in collecting data. The research population was the students of tenth grade they were X.1 class and X.2 class consist of 46 students, so the researcher took random sampling technique. The data were analyzed by finding the mean score. For collecting the data, the researcher used one instrument namely descriptive writing test to measure the students’ writing ability. The result of this research showed that the student’ writing description was low classification in pre-test with the mean score 64.6 for experimental class and the mean score of control class was 60.8, and it was average categorized. However, after doing the treatment through outdoor learning strategy they got good classification for Experimental group and still average classification for control group in post-test; their mean score had increased up to 78.4, for Experimental and 69.9 for control group. The data was analyzed by using t-test and the result showed that the t-test value 4.037 was higher than t-table value 2.021. It meant that there was a significance difference of students’ writing ability before and after the treatment through the application of outdoor learning. It concluded that outdoor learning strategy can be used in improving writing description of the students.